Growth and spawning of nemipterus furcosus in the coastal water of Pahang, Malaysia - Amira Farzana binti Samat (Kulliyyah of Science, International Islamic University Malaysia, 2014)
Nemipterus furcosus, commonly known as fork-tail threadfin bream is an economically important food fish in Malaysia but the capture production of this fish is decreasing gradually in the Malaysian water. However, nothing is known about the population of this species in the Malaysian water especially in the coastal of Pahang. Therefore, this study aimed to understand some important characteristics of fork-tail threadfin bream population in the coastal water of Pahang. Monthly samples were collected from commercial fishing trawlers for a period of one year (August 2012 - July 2013). A total of 1599 threadfin bream specimens were studied in this research. The results showed that male threadfin bream was significantly more than female (p<0.01) in the population of Pahang coastal water. The mathematical relationship between length and weight of fork-tail threadfin bream of each month was significant (p<0.05) with all coefficients of determination (R2) values being higher than 0.7799 for male, while 0.5091 for female. The growth coefficient (b value) varied between 2.6808 (May) and 3.333 (October) for male and 2.0926 (September) and 3.2464 (November) for female N. furcosus. A negative allometric growth of N. furcosus was observed from February until June, and September for female while in January, March until June, and November for male N. furcosus. Positive allometric growth was observed in remaining month of both male and female N. furcosus. The growth coefficients were very low in September for female and in May for male compared to other months. The significantly (P<0.05) lowest mean condition factor was found in July (1.2559) and the highest in August (1.3917) for male while lowest in March (1.2503) and highest in August (1.3926) for female N. furcosus. Overall higher mean condition factor was observed in smaller fish of both sexes. The overall mean condition factor of male and female was statistically similar (p>0.05). Mean gonadosomatic index (GSI) of female was higher than male in all months. GSI of female N. furcosus was highest in June while male in November. Gonadosomatic index of female rapidly increased after December and reached at peak in June and decline after June. Histological observation of gonads also showed reasonably similar stages of maturation in both male and female. N. furcosus showed immature gonadal stage in October and November. After that, they enter the maturing stage in December, January and February and mature in March. After the mature stage, N. furcosus testes and ovaries enter the ripe and running stage in April, May, June and July. Then, the gonad spent in August and finally enters the resting stage in September. The spawning season of threadfin bream in Pahang coastal water was from January to August. Histological study indicated that the peak spawning season occurs from April to July. This study indicated that the histological study is very useful to understand the peak spawning period of fish. The results of the study will help the management of juvenile and breeding N. furcosus stock in order to maintain sustainable exploitation in the coastal water of Pahang.